(untitled) (Journal of Chemical Engineering, 2017)
Global warming and depletion of fossil fuel enhances people to obtain alternative clean sources of energy. The key objective of this study was to develop adsorbent systems for sulphur (from H2S) and siloxanes removal from the anaerobic digestion gas (ADG) by commercially available adsorbents for a solid oxide fuel cell (SOFC) application. The target limits for removal of sulphur and siloxane compounds were less than 1 ppmv and 100ppbv respectively for the SOFC application. Based on the results of this work (this work is a part of a European Union project named SOFcom) and some other projects of SOFcom, a pilot plant of SOFC (capacity 100 kW fuel energy) will attempt to operate using the ADG produced from the Torino Sewage Plant, Italy. Different types of siloxanes were available in the ADG, among them D5 was chosen as representative for their higher concentrations (1200ppbv) in Torino, Italy. However, all types of siloxanes are also possible to remove from ADG by the same adsorbent. Commercially available adsorbents such as Activated Carbon (sigma), Zeolite 5A, FCDS GS-1(ZnO) and FCDS GS6, Active carbon (Norit RST3) and Soxsia were explored in the fixed bed reactor in laboratory. Artificially simulated ADG was tested in the laboratory (for simplicity) to determine the adsorption capacities of adsorbents. FCDS GS-1 (48 mg/g) and Norit RST3 (55.7 mg/g) were performed as best adsorbents for sulphur and siloxane D5 removal respectively. Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 40-43